Commodification of INews News Narrative Content on Perceptions of 2024 Election Fraud - Ramdani, Muhammad Zidan; Nabiilah, Adinda Syahlaa; Ramadhania, Bunga Putri; Bilqis, Tazkiyatul Fikriyah; Khoirotunnisa, Pia (Journal of Social Science and Education Research, 2024)
This study explores the commodification of INews news narrative content towards the perception of fraud in the 2024 Election. The main problem underlying this study is the increasing public concern about honesty in the election process, which is often influenced by media coverage. This study aims to analyze how INews, as one of the main media, packages news related to alleged fraud in the 2024 Election and its impact on public perception. The method used is content analysis with a qualitative approach, where news is taken from the campaign period to post-election. Data is analyzed using discourse analysis techniques to identify themes, narratives, and news framing. The results of the study show that INews tends to commodify news by emphasizing sensational and dramatic aspects, which can strengthen negative perceptions of election fraud among the public. The conclusion of this study is that the commodification of news by INews can significantly influence public opinion, so it is important for the media to maintain objectivity and integrity in election reporting to support a healthy democratic process.